SOLVING PROBLEM SUPPLY CHAIN IN COMPANY WITH SUPPLY CHAIN MANAGEMENT - Edo Habib Maulana; Ala' Odeh; Christopher J.E. Siwi (AIBPM Publisher, 2018)
Supply Chain Management (SCM) is the management of a supply chain activities to maximize customer value and achieve a sustainable competitive advantage. It acts as a strategic competitive tool for the company that made the issue of logistics as a strategy to compete to be able to win the market competition. The purpose of this paper is to analyze the effectiveness of the Supply Chain Management implemented by a manufacture company in Indonesia. The results then will be advised to the owner to improve the existing supply chain management. Keywords: Supply Chain, Supply Chain Management (SCM), manufacturing